Transforming History Education: Implementing Project-Based Learning Under the Merdeka Curriculum at SMK Yos Sudarso Rembang - Amalia Devita Pratiwi; Khoirul Huda (Tarikhuna: Journal of History and History Education, 2025)
This study addresses the ongoing problem of passive student engagement in history lessons caused by traditional teacher-centered methods at SMK Yos Sudarso Rembang. This study examines the implementation of Project-Based Learning (PBL) in history classes under the Merdeka Curriculum, aiming to enhance students’ motivation, comprehension, and 21st-century skills by promoting active participation, collaboration, and critical thinking. Using a qualitative case study design, data were collected through structured interviews, observations, and document analysis over five months. The findings reveal that PBL enhances student engagement, motivation, and comprehension of historical material, supported by interactive group activities and project presentations. However, challenges such as aligning projects with diverse student needs, managing time effectively, and providing clear guidelines were identified. Teachers also faced difficulties adapting to facilitative roles and addressing the logistical demands of PBL. Despite these obstacles, PBL demonstrated significant potential in fostering essential 21st-century skills, aligned with the goals of the Merdeka Curriculum. This study concludes that strategic teacher training, improved resource allocation, and practical real-world applications can optimize PBL in history education and beyond. Future research should explore quantitative analyses and the long-term impact of PBL on educational outcomes across various subjects and contexts.